PARTISIPASI MASYARAKAT DALAM PENGELOLAAN HUTAN KEMASYARAKATAN (HKm) TANDUNG BILLA DI KELURAHAN BATTANG KOTA PALOPO - Witno Witno; Maria Maria; Dicky Supandi (Jurnal Penelitian Kehutanan BONITA, 2020)
In an effort to realize the concept of sustainable forest management, it is necessary to involve the community around the forest as the main actors who often interact with the forest. In this case, the concept in question is the concept of community participation. This study aims to determine the participation of forest communities in the existence of community forests. This research was conducted in Battang Village, West Wara District, Palopo City, South Sulawesi Province. Data was obtained directly through surveys and direct field observations, data collected through the observation method and semi-structured interviews were processed and clarified according to the research objectives and then analyzed using qualitative data analysis. The results obtained by community participation in community forestry are the lack of community participation which initially numbered 137 people, only 35 people left who were active due to contradictory plans and conditions in the field that triggered problems in the group.